The Effect of Caramelization and Carbonization Temperatures toward Structural Properties of Mesoporous Carbon from Fructose with Zinc Borosilicate Activator - Tutik Setianingsih; Indriana Kartini; Yateman Arryanto (Universitas Gadjah Mada, 2014)
Mesoporous carbon was prepared from fructose using zinc borosilicate (ZBS) activator. The synthesis involves caramelization and carbonization processes. The effect of both process temperature toward porosity and functional group of carbon surface are investigated in this research. The caramelization was conducted hydrothermally at 85 and 100 °C, followed by thermally 130 °C. The carbonization was conducted at various temperatures (450–750 °C). The carbon-ZBS composite were washed by using HF 48% solution, 1M HCl solution, and aquadest respectively to remove ZBS from the carbon. The carbon products were characterized with nitrogen gas adsorption-desorption method, FTIR spectrophotometry, X-ray diffraction, and Transmission Electron Microscopy. The highest mesopore characteristics is achieved at 100 °C (caramelization) and 450 °C (carbonization), including Vmeso about 2.21 cm3/g (pore cage) and 2.32 cm3/g (pore window) with pore uniformity centered at 300 Å (pore cage) and 200 Å (pore window), containing the surface functional groups of C=O and OH, degree of graphitization about 57% and aromaticity fraction about 0.68.